Cultivo in vitro de fragmento ovariano bovino suplementado com nanocompósitos de óxido de zinco dopados com óxido de cálcio ou óxido de magnésio - Soares, Mayara Mafra (2023)
The aim of this study was to test the influence of supplementing the in vitro culture medium with Nanocomposites (NCs) of zinc oxide doped with magnesium chloride (ZnO: 0.5 Mg-MgO) and NCs of zinc oxide doped with calcium chloride (ZnO: 0.5 Ca-CaO), compared to the pure supplementation of these minerals MgCl2 and CaCl2, in three concentrations 10, 20 and 30 µg/ml on the viability of bovine ovarian tissue fragments cultured in vitro. For this purpose, 2 experiments were carried out with the following treatments: 1) Fresh Control (CF), Control (CONT), 10 µg/mL of calcium chloride (CaCl2) (CA10), 20 µg/mL of CaCl2 (CA20), 30 µg/mL of CaCl2 (CA30), 10 µg/mL of ZnO NP:0.5Ca (NPCA10), 20 µg/mL of ZnO NP:0.5Ca (NPCA20), 30 µg/mL of ZnO NP:0.5Ca (NPCA30); 2) CF, CONT, 10 µg/mL magnesium chloride (MgCl2) (MG10), 20 µg/mL MgCl2 (MG20), 30 µg/mL MgCl2 (MG30), 10 µg/mL ZnO NP:0.5Mg (NPMG10), 20 µg/mL ZnO NP:0.5Mg (NPMG20), 30 µg/mL ZnO NP:0.5Mg (NPMG30). Cell degeneration, respiratory metabolism of cells by NAD and FAD emission, redox state, ROS production and finally follicular activation and viability were analyzed. For statistical analysis, SigmaPlot version 11.0 software (Systat Software, Inc., USA) was used, applying analysis of variance and Fisher's LSD post hoc test to compare means, with significance P < 0.05. The NPCA20 treatment showed higher levels of cell degeneration, higher ROS production and lower NAD(P)H and FAD emission, compared to CF and its respective CA20 treatment. The NPMG20 treatment showed a lower rate of cell degeneration, higher NAD and FAD production, lower ROS production and good follicular viability when compared to the controls and MG20. Thus, it is concluded that ZnO:0.5Ca NP at a concentration of 20 μg/mL impaired cell and follicular development, proposing cytotoxic effects in the culture of bovine ovarian cortex fragments. In the second experiment, the doping process was efficient in the ZnO:0.5Mg NP, providing a favorable environment for cellular and follicular development, as the doping process and the correct combination of ions reverse a possible toxicity scenario.